The use of the radial styloid in the extended osteocutaneous radial forearm free flap. Issue 2 (June 2016) - Matthews, Jennifer; Ng, Wendy; Archibald, Stuart; Levis, Carolyn
Background: The osteocutaneous radial forearm free flap (OC-RFFF) remains a useful tool in head and neck reconstruction; however, it can be challenging to harvest sufficient bone for large reconstructions. The extended OC-RFFF is a modification that involves harvest of the distal border of the radius to the tip of the styloid. This increases the length of the bone flap by 2 cm to 3 cm, and the inherent contour of the styloid can be used to reconstruct the anterior curvature of the mandible or maxilla without additional osteotomies that may reduce blood supply. Methods: The key steps in harvesting the extended OC-RFFF are described. Six patients with mandibular or maxillary defects underwent reconstruction with the extended OC-RFFF. Patient data including demographics, defect features, reconstruction details and outcomes were collected. Results: Of the six patients who underwent the extended OC-RFFF, four had mandibular reconstruction and two had maxillary reconstruction. Two patients underwent reconstruction for osteoradionecrosis and the remainder for malignant disease. The average patient age at the time of surgery was 64.5 years. The length of radius harvested ranged from 8 cm to 14 cm (mean 9.7 cm). Two of six patients required a single osteotomy of their bone flap. Donor site complications included partial skin graft loss in 50% and a radius fracture in two patients. Recipient site complications included one patient with intraoral plate exposure. There have been no cases of nonunion. Conclusions: The extended OC-RFFF was a safe and reliable option for bony reconstruction in the head and neck.